Simulation of fluid flow dynamics in designing a bi-ventricular assist device using CFD tools - Sadaf, Lamiya; Hoque, Walia; Zaima, Nazifa Tabassum (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2019.